2009
DOI: 10.5194/npg-16-131-2009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of third-order nonlinearity on statistical properties of random directional waves in finite depth

Abstract: Abstract. It is well established that third-order nonlinearity produces a strong deviation from Gaussian statistics in water of infinite depth, provided the wave field is long crested, narrow banded and sufficiently steep. A reduction of thirdorder effects is however expected when the wave energy is distributed on a wide range of directions. In water of arbitrary depth, on the other hand, third-order effects tend to be suppressed by finite depth effects if waves are long crested. Numerical simulations of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 42 publications
5
38
0
Order By: Relevance
“…Short-crested wave fields on deep water have nearGaussian statistics despite the nonlinearity of the wave field (Onorato et al, 2002;Socquet-Juglard et al, 2005;Gramstad and Trulsen, 2007;Onorato et al, 2009). In shallower water, however, Toffoli et al (2009) suggested that when directional components are taken into account, the probability of freak waves is notably increased compared to long-crested waves. In this paper we do not consider the effect of shortcrestedness.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Short-crested wave fields on deep water have nearGaussian statistics despite the nonlinearity of the wave field (Onorato et al, 2002;Socquet-Juglard et al, 2005;Gramstad and Trulsen, 2007;Onorato et al, 2009). In shallower water, however, Toffoli et al (2009) suggested that when directional components are taken into account, the probability of freak waves is notably increased compared to long-crested waves. In this paper we do not consider the effect of shortcrestedness.…”
Section: Introductionmentioning
confidence: 99%
“…In deep water it is known that third-order nonlinearity can cause focusing of long-crested and narrow-banded waves, and can be responsible for the occurrence of freak waves (Onorato et al, 2001(Onorato et al, , 2005Mori and Yasuda, 2002;Janssen, 2003;Mori and Janssen, 2006;Toffoli et al, 2008Toffoli et al, , 2009. As nonlinear modulation is reduced for long-crested waves on shallower depths, it may be anticipated that there is a corresponding reduction in the probability of freak waves Janssen and Onorato, 2007;Toffoli et al, 2009;Janssen, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond this threshold, nevertheless, oblique perturbations still remain unstable and numerical simulations of the 2 + 1 NLS equation, in this respect, confirm that such modes can still trigger very large amplitude waves (Slunyaev et al, 2002;Didenkulova et al, 2013). Furthermore, direct numerical simulations of the Euler equation also indicate that directional components can sustain the formation of extreme waves in random directional wave fields in water of finite depth, leading to substantial deviations from standard second-order based statistics (Toffoli et al, 2009).…”
Section: Introductionmentioning
confidence: 82%